The role of mitogen-activated protein kinases and sterol receptor coactivator-1 in TGF-β-regulated expression of genes implicated in macrophage cholesterol uptake - Salter, Rebecca C. (Sci Rep, 2016)
The anti-atherogenic cytokine TGF-β inhibits macrophage foam cell formation by suppressing the expression of key genes implicated in the uptake of modified lipoproteins. We have previously shown a critical role for p38 MAPK and JNK in the TGF-β-mediated regulation of apolipoprotein E expression in human monocytes. However, the roles of these two MAPK pathways in the control of expression of key genes involved in the uptake of modified lipoproteins in human macrophages is poorly understood and formed the focus of this study. TGF-β activated both p38 MAPK and JNK, and knockdown of p38 MAPK or c-Jun, a key downstream target of JNK action, demonstrated their requirement in the TGF-β-inhibited expression of several key genes implicated in macrophage lipoprotein uptake. The potential role of c-Jun and specific co-activators in the action of TGF-β was investigated further by studies on the lipoprotein lipase gene. c-Jun did not directly interact with the minimal promoter region containing the TGF-β response elements and a combination of transient transfection and knock down assays revealed an important role for SRC-1. These studies provide novel insights into the mechanisms underlying the TGF-β-mediated inhibition of macrophage gene expression associated with the control of cholesterol homeostasis.